From Hometown Clubs to Transnational Social Movement: The Evolution of Oaxacan Migrant Associations in California - Rivera Salgado, Gaspar (Social justice, 2015)
The article discusses the formation and evolution of Oaxacan immigrant-led social movements in California, with emphasis on Frente Indígena de Organizaciones Binacionales (FIOB) or the Binational Front of Indigenous Organization. Topics discussed include the evolution of hometown associations to transnational movements, the history of migration of Oaxaca indigenous people, and the fight of FIOB for human rights and political rights.